BMI1 enables interspecies chimerism with human pluripotent stem cells - Ke Huang (Nature Portfolio, 2018)
Conventional human pluripotent stem cells (hPSCs) fail to contribute to interspecies chimaeras when injected into mouse blastocysts. Here the authors show that forced expression of BMI1 overcomes apoptosis of hPSCs in blastocysts of mouse, rabbit and pig allowing them to contribute to chimaeras.